Association of ABCB1, ABCG2 drug transporter polymorphisms and smoking with disease risk and cytogenetic response to imatinib in chronic myeloid leukemia patients. (March 2023) - Mohammadi, Fatemeh; Rostami, Golale; Hamid, Mohammad; Shafiei, Mohammad; Azizi, Masoumeh; Bahmani, Hasan
Abstract: Background: Despite acceptable results of imatinib in the treatment of chronic myeloid leukemia (CML), some patients fail to acquire a complete cytogenetic response (CCyR), which may be caused by polymorphisms in the pharmacogenetic genes. The study aimed to evaluate the association of two polymorphisms in the ABCB1 and ABCG2 genes with cytogenetic response to imatinib and the risk of CML development. Methods: We genotyped ABCB1 (c .2677G/T/A) and ABCG2 (c .421C/A) polymorphisms by PCR-RFLP, T-ARMS-PCR methods in 111 patients with CML and 102 sex- and age-matched healthy subjects. CCyR was determined by standard chromosome banding analysis (CBA). Results: Analysis of polymorphisms showed significant association of ABCG2 c.421CA genotype (p < 0.0001; OR = 0. 17), and ABCG2 c.421A allele (p < 0.0001; OR = 0.31) with decreased risk of CML. Moreover, ABCB1 c.2677GT- ABCG2 c.421CC combined genotype (p = 0.017; OR = 4.20) was associated with increased risk of CML. Analysis of the joint effect of SNP-smoking combination showed that smoker subjects with the ABCB1 c.2677GG/GT (p = 0.001; OR = 15.96, p = 0.001; OR = 8.13, respectively) or ABCG2 c.421CC genotypes (p = 0.001; OR = 5.82) had the increased risk of CML, while the risk of the CML in non-smokers carrying the ABCG2 c.421CA (p < 0.0001; OR = 0. 18) genotype was strongly decreased compared with reference group. Regarding drug response, ABCG2 c.421 CC/CA genotypes in the smoker patients were associated with an increased risk of resistance to imatinib (p < 0.0001; OR = 7.02, p = 0.018; OR = 4.67, respectively). Conclusion: Our results suggest the impact of ABCG2c .421C/A polymorphism on CML development, and smoking may have a synergistic role in the risk of CML and resistance to imatinib. Highlights: We found protective effect of ABCG2 c.421CA genotype, ABCG2 c.421A allele on CML risk. No association between ABCB1 c .2677G/T/A and ABCG2c .421C/A genotypes with IM response. The smokers with ABCG2c.421 CC/CA genotypes increased risk of IM resistance. ABCB1 c.2677GT- ABCG2 c.421CC diplotype was associated with 4.2 times more risk of CML. The CML risk in smokers with ABCB1 c.2677GG/GT, ABCG2 c.421CC genotypes was 5–15 fold.